Randomized clinical trial of the effect of NovaMin and CPP-ACPF in combination with dental bleaching - Larissa Dias ALEXANDRINO; Cristiane de Melo ALENCAR; Ana Daniela Silva da SILVEIRA; Eliane Bemerguy ALVES; Cecy Martins SILVA
Abstract Objective This randomized, controlled, double-blind clinical study evaluated the effect of calcium sodium phosphosilicate (NovaMin) and casein phosphopeptide-amorphous calcium phosphate with fluoride (CPP-ACPF) on the prevention of post-operative sensitivity and on the effects of clinical bleaching treatment. Material and Methods Sixty volunteers were selected according to inclusion and exclusion criteria and were randomly assigned into three groups (n=20): CG (control group) patients, who were treated with 35% hydrogen peroxide; NOVAG (NovaMin group) patients, who were treated with 35% hydrogen peroxide followed by the application of NovaMin; and CPPG (CPP group) patients, who were treated with 35% hydrogen peroxide followed by the application of CPP-ACPF. Both bioactive agents were applied for five minutes. An evaporative stimulus associated with a modified visual scale was used to analyze sensitivity 24 hours after each bleaching session. The color evaluation was performed on the maxillary central incisors using a spectrophotometer. Associations between the intervention group, bleaching session, and reported sensitivity were tested using Chi-square partitioning. Results Color change values (ΔE) were analyzed using analysis of variance (ANOVA). The significance level used for both tests was 5%. In the intragroup assessment, the Friedman test showed that only the CPP-ACPF group showed no statistically significant difference (p<0.05) between baseline and first bleaching session. In the intergroup assessment, the Kruskal-Wallis test showed that the CPPG had less postoperative sensitivity after the first session, when compared to the other groups (p<0.05). Color change analysis (ΔE) showed a significant difference between the means obtained in the different bleaching sessions in all groups (p<0.05). Conclusions This study showed that the combination of CPP-ACPF with 35% hydrogen peroxide significantly reduced post-operative sensitivity in the first session, compared with the other evaluated treatments. The association of CPP-ACPF and NovaMin did not affect the color change induced by tooth bleaching.